A case of replantation of deciduous upper central incisors under different extra-alveolar conditions. Issue 3 (December 2015) - Isogawa, Nobutaka; Ito, Kaori; Ikeda, Masakazu; Ishikawa, Masaaki
Abstract: Purpose: The extra-alveolar condition of an avulsed tooth is important for its successful replantation. Here we report a case of deciduous incisors replantation under different extra-alveolar conditions. Case report: Traumatically avulsed upper deciduous central incisors of a 3-year-old girl were replanted. Two hours before replantation, the left incisor was in a moist condition, while the right one was dry. After 3 years, we found that the deciduous incisors were correctly replaced by their successors. Conclusion: The difference in extra-alveolar conditions between both avulsed deciduous central incisors did not produce significant differences between them after replantation.